Editorial introduction to 'Collectivist planning' by Michael Polanyi (1940). Issue 6 (December 2019) - Hodgson, Geoffrey M.; Polanyi, Michael
Abstract: After an esteemed academic career as a chemist, Michael Polanyi switched to the social sciences and made significant contributions to our understanding of the nature and role of knowledge in society. Polanyi's argument concerning knowledge led him to emphasise the vital importance of decentralised mechanisms of adjustment and coordination, including markets. His article 'Collectivist Planning' (1940) enters into debates about the possibility (or otherwise) of centrally planning scientific and economic activity. This early article also foreshadows post-war debates within the Mont Pèlerin Socierty (formed in 1947) concerning the economic role of the state and the future of liberalism.